Declines in stillbirth and neonatal mortality rates in Europe between 2004 and 2010: results from the Euro-Peristat project. Issue 6 (30th December 2015) - Zeitlin, Jennifer; Mortensen, Laust; Cuttini, Marina; Lack, Nicholas; Nijhuis, Jan; Haidinger, Gerald; Blondel, Béatrice; Hindori-Mohangoo, Ashna D
Abstract : Background: Stillbirth and neonatal mortality rates declined in Europe between 2004 and 2010. We hypothesised that declines might be greater for countries with higher mortality in 2004 and disproportionally affect very preterm infants at highest risk. Methods: Data about live births, stillbirths and neonatal deaths by gestational age (GA) were collected using a common protocol by the Euro-Peristat project in 2004 and 2010. We analysed stillbirths at ≥28 weeks GA in 22 countries and live births ≥24 weeks GA for neonatal mortality in 18 countries. Per cent changes over time were assessed by calculating risk ratios (RR) for stillbirth, neonatal mortality and preterm birth rates in 2010 vs 2004. We used meta-analysis techniques to derive pooled RR using random-effects models overall, by GA subgroups and by mortality level in 2004. Results: Between 2004 and 2010, stillbirths declined by 17% (95% CI 10% to 23%), with a range from 1% to 39% by country. Neonatal mortality declined by 29% (95% CI 23% to 35%) with a range from 9% to 67%. Preterm birth rates did not change: 0% (95% CI −3% to 3%). Mortality declines were of a similar magnitude at all GA; mortality levels in 2004 were not associated with RRs. Conclusions: Stillbirths and neonatal deaths declined at all gestational ages in countries with both high and low levels of mortality in 2004. These results raise questions about how low-mortality countries achieve continued declines and highlight the importance of improving care across the GA spectrum.